SELEKSI DAN PERSILANGAN AYAM KAMPUNG DI DESA SERUAWAN KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Papilaya, Bercomien Juliet; Sarfan, Riri; Rajab, Rajab; Joris, Lily (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Native chickens are among the livestock commonly raised in rural areas and have great potential to meet household food needs and supplement family income. Seruawan Village, located at an altitude of 5–10 meters above sea level, borders Kamarian Village to the east, Kairatu Village to the west, the Seram Sea to the south, and the mountains to the north. Poultry farming in this area is generally traditional, with limited human intervention in management, such as simple housing, ownership, and the provision of basic supplementary feed like kitchen waste. This community service program aims to increase the productivity of native chickens through the selection of superior breeding stock and the utilization of fishery and agricultural waste. The specific objectives are: (1) to improve farmers’ knowledge and skills in crossbreeding and selective breeding using superior strains such as KUB, super, and Bangkok chickens; (2) to train and motivate farmers to enhance management systems and become local breeders; and (3) to encourage proper record-keeping practices. The program targets local poultry farmer groups who are willing to adopt new innovations to improve production and family welfare. Its success is reflected in farmers’ increased attention and active participation during training and demonstration activities.